CLUSTERS OF PREVALENT PATTERNS OF GEOMETRIC THINKING LEVELS AMONG MATHEMATICS STUDENTS - Joshua Edson Gorme Ordiz; Ghanine Rhea Mecate (IKIP Siliwangi and I-MES, 2022)
Geometric thinking skills are the perceived abilities of an individual to think and reason in geometric contexts. These skills acquired by students in geometry remain poor and unsettling because of the misconceptions that hinder the students in learning the components of geometry. The study described the common unplaceable patterns in geometric thinking of 153 mathematics education students in a state university in Eastern Visayas, Philippines. Frequency Analysis was employed in the study to determine the number of occurrences of the patterns stressing the cause for students placed under level 0 or unplaceable. Van Hiele Achievement Test was used to gather the students’ performance in geometry at all levels, namely: visualization, analysis, informal deduction, deduction, and rigor. The findings attested that only 13.1% of the students managed the third level of the Van Hiele Levels while 43.1% of them were unplaceable. Common patterns were drawn and describe to understand the consequences in geometric thinking ability at level 0. These observable patterns were grouped into core-remedial, topical-corrective, and close-corrective groups. The clusters will enable educational institutions to address the individual gaps in geometry.